Factors Affecting Arteriovenous Fistula (AVF) Maturation - Nabila, Cahya; Khairunnisa, Salwa; Sajidah, Holila (Jurnal KESANS : Kesehatan dan Sains, 2021)
AVF requires postoperative maturation before cannulation to initiate hemodialysis treatment. AVF maturation usually takes about six weeks and depends on the development of vascular remodeling. However, AVF surgery is not always followed by successful maturation. Recent studies have shown that the rate of maturation failure in patients with chronic kidney disease undergoing AVF-type vascular access establishment is very high, ranging from 20% to 60%. The source search was carried out on the online portal of journal publications as many as 12 sources from Medscape, Google Scholar, National Center for Biotechnology Information (NCBI) with the keywords chronic kidney disease, hemodialysis, AVF, and maturation. Many factors are involved in the functional maturation of AVF, including age, sex, coagulation factors, lipid profile, hypoalbumin, venous diameter, diabetes, hypertension, peripheral vascular disease, smoking, obesity, and dialysis. Failure of AVF maturation results in insufficient blood flow to allow cannulation and initiation of hemodialysis.